Comparison of 5-HT3 or 5-HT4 agents function into the prelimbic area on passive avoidance memory consolidation - Ahmadi-Mahmoodabadi, Nargol; Nasehi, Mohammad; Emamghoreishi, Masoumeh; Zarrindast, Mohammad-Reza (Archives of Advances in Biosciences, 2016)
Growing evidence suggests that serotonin plays an important role in learning and memory and all its receptors might be implicated in this process. The present study aimed at investigating and comparing the possible involvement of 5-HT3 and 5-HT4 receptor (R) agonists/antagonists upon consolidation of inhibitory avoidance memory in the pre-limbic (PL) area. Bilateral intra-PL microinjections of m-CPBG (m-Chlorophenylbiguanide hydrochloride: a selective 5-HT3R agonist; 0.1 μg/rat), Y-25130 (a selective 5-HT3R antagonist; 0.1 μg/rat), RS67333 (a potent and highly selective 5-HT4R partial agonist; 0.5 μg/rat) and RS23597-190 (a selective 5-HT4R antagonist; 0.5 μg/rat) were performed immediately after training. The step-through inhibitory avoidance (IA) task was used to memory assessment in adult male Sprague-Dawley rats. Our data revealed that the post-training intra-PL microinjection of m-CPBG relative to saline and Y-25130 decreased inhibitory avoidance memory consolidation in the PL area. On the contrary, RS67333 increased IA memory consolidation in comparison to saline and RS23597-190. In addition, there was also a significant difference between the effects of m-CPBG and RS67333 on IA memory consolidation in the PL area. M-CPBG induced reduction of IA memory consolidation, while RS67333 increased it. However, Y-25130 compared to RS23597-190 did not show any significant difference. All above interventions did not alter locomotor activity. This study indicated that local direct agonist activation of 5-HT3Rs induced the reduction of IA memory consolidation, opposed to the local direct agonist activation of 5-HT4Rs, which mediated enhancement of IA memory consolidation. It can be proposed that 5-HT3Rs in comparison to 5-HT4Rs may be inversely involved in modulation of IA memory consolidation in the PL.